Attitude And Peer Influence Associated With Drug Abuse Among Residents In West Baturaja District: A Cross-Sectional Study - Apria Wilinda Sumantri (International Journal of Health Engineering and Technology, 2026)
Drug abuse remains a public health problem that requires attention because it affects individual health, family stability, and community safety. This study aimed to analyze the association between attitude, peer influence, and drug abuse among residents in West Baturaja District. This study used a quantitative analytic design with a cross-sectional approach. The study was conducted in West Baturaja District, Ogan Komering Ulu Regency, South Sumatra, Indonesia, from February to April 2026. The sample consisted of 56 respondents selected using accidental sampling. Data were collected using a structured questionnaire and checklist, then analyzed using univariate analysis and Chi-square test with a significance level of 0.05. The results showed that 32 respondents (57.1%) were classified as positive for drug abuse, 27 respondents (48.2%) had negative attitudes, and 34 respondents (60.7%) were exposed to negative peer influence. The Chi-square test showed a significant association between attitude and drug abuse (p = 0.028) and between peer influence and drug abuse (p = 0.001). This study concludes that attitude and peer influence are significantly associated with drug abuse among residents in West Baturaja District. Community-based prevention should strengthen protective attitudes, peer control, family supervision, and continuous health education.